NRP2 and CD63 Are Host Factors for Lujo Virus Cell Entry - Raaben, Matthijs; Jae, Lucas T; Herbert, Andrew S; Kuehne, Ana I; Stubbs, Sarah H; Chou, Yi-Ying; Blomen, Vincent A; Kirchhausen, Tomas; Dye, John M; Brummelkamp, Thijn R; Whelan, Sean P (Cell host & microbe, 2017)
Arenaviruses cause fatal hemorrhagic disease in humans. Old World arenavirus glycoproteins (GPs) mainly engage α-dystroglycan as a cell-surface receptor, while New World arenaviruses hijack transferrin receptor. However, the Lujo virus (LUJV) GP does not cluster with New or Old World arenaviruses. Using a recombinant vesicular stomatitis virus containing LUJV GP as its sole attachment and fusion protein (VSV-LUJV), we demonstrate that infection is independent of known arenavirus receptor genes. A genome-wide haploid genetic screen identified the transmembrane protein neuropilin 2 (NRP2) and tetraspanin CD63 as factors for LUJV GP-mediated infection. LUJV GP binds the N-terminal domain of NRP2, while CD63 stimulates pH-activated LUJV GP-mediated membrane fusion. Overexpression of NRP2 or its N-terminal domain enhances VSV-LUJV infection, and cells lacking NRP2 are deficient in wild-type LUJV infection. These findings uncover this distinct set of host cell entry factors in LUJV infection and are attractive focus points for therapeutic intervention.